2003
DOI: 10.1046/j.1365-2672.2003.01959.x
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage continuous culture system to study the effect of supplemental alpha-lactalbumin and glycomacropeptide on mixed cultures of human gut bacteria challenged with enteropathogenic Escherichia coli and Salmonella serotype Typhimurium

Abstract: Aims: Certain milk factors may promote the growth of a gastrointestinal microflora predominated by bifidobacteria and may aid in overcoming enteric infections. This may explain why breast-fed infants experience fewer intestinal infections than their formula-fed counterparts. The effect of formula supplementation with two such factors was investigated in this study. Methods and Results: Infant faecal specimens were used to ferment formulae supplemented with glycomacropeptide (GMP) and a-lactalbumin (a-la) in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Molar proportions of the different SCFA measured in our fecal cultures were within the same order of that reported by others. Thus, most authors indicated that acetic acid is produced at higher levels than propionic and butyric acids (1,4,9,25,46). Incubation of the intestinal microbiota in the presence of our EPS or inulin promoted a shift in the SCFA profile of fecal cultures, causing a decrease through the incubation of molar proportions of acetic acid, an increase in propionic acid levels, decreases or moderate increases in butyric acid levels, and a reduction in the acetic acid-to-propionic acid ratio through time.…”
Section: Discussionmentioning
confidence: 99%
“…Molar proportions of the different SCFA measured in our fecal cultures were within the same order of that reported by others. Thus, most authors indicated that acetic acid is produced at higher levels than propionic and butyric acids (1,4,9,25,46). Incubation of the intestinal microbiota in the presence of our EPS or inulin promoted a shift in the SCFA profile of fecal cultures, causing a decrease through the incubation of molar proportions of acetic acid, an increase in propionic acid levels, decreases or moderate increases in butyric acid levels, and a reduction in the acetic acid-to-propionic acid ratio through time.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of milk with 2% CMP, either of bovine, ovine or caprine origin, increased the counts of B. lactis by 1.5 log cycles after 24 h incubation at 37 1C when compared with unsupplemented milk (Janer, Pela´ez, & Requena, 1994). The ability of CMP to nourish healthy gut microflora points at its potential as a prebiotic in functional foods, or as a supplement in infant formulae to simulate the beneficial bacteriological effects of breast milk (Bruck, Graverholt, & Gibson, 2003a;Bruck et al, 2003b). Dietary intake of CMP as a source of NANA was found to increase the sialic acid content of the saliva in piglets, which influences its viscosity and protective properties (Wang et al, 2004).…”
Section: Health Effects Of Intact Cmpmentioning
confidence: 97%
“…caseinomacropeptide, may help to promote growth of a host-friendly colonic microflora, mainly bifidobacteria or lactobacilli, and may help to overcome some enteric infections (Bruck, Graverholt, & Gibson, 2003;.…”
Section: Article In Pressmentioning
confidence: 99%